2018
DOI: 10.5194/gmd-11-575-2018
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory errors of different numerical integration schemes diagnosed with the MPTRAC advection module driven by ECMWF operational analyses

Abstract: Abstract. The accuracy of trajectory calculations performed by Lagrangian particle dispersion models (LPDMs) depends on various factors. The optimization of numerical integration schemes used to solve the trajectory equation helps to maximize the computational efficiency of large-scale LPDM simulations. We analyzed global truncation errors of six explicit integration schemes of the Runge-Kutta family, which we implemented in the Massive-Parallel Trajectory Calculations (MPTRAC) advection module. The simulation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 41 publications
2
21
0
Order By: Relevance
“…Hoffmann et al (2017) presented an intercomparison of meteorological analyses and an evaluation of MPTRAC trajectory calculations with super-pressure balloon observations for the Antarctic lower stratosphere. Rößler et al (2018) evaluated trajectory errors of different numerical integration schemes diagnosed with the MPTRAC advection module driven by highresolution ECMWF operational analyses and forecasts.…”
Section: Lagrangian Transport Modelsmentioning
confidence: 99%
“…Hoffmann et al (2017) presented an intercomparison of meteorological analyses and an evaluation of MPTRAC trajectory calculations with super-pressure balloon observations for the Antarctic lower stratosphere. Rößler et al (2018) evaluated trajectory errors of different numerical integration schemes diagnosed with the MPTRAC advection module driven by highresolution ECMWF operational analyses and forecasts.…”
Section: Lagrangian Transport Modelsmentioning
confidence: 99%
“…Roughly, these layers cover the free troposphere (2 -8 km), the upper troposphere and lower stratosphere (UT/LS, 8 -16 km), the lower and middle stratosphere (16 -32 km), and the middle and upper stratosphere (32 -48 km). Rößler et al (2018) found that trajectory errors within different height layers also vary with latitude and season. We therefore evaluated the simulation results not only globally, but also in three latitude bands, covering .…”
Section: Simulation Setup and Overview Of Numerical Experimentsmentioning
confidence: 98%
“…Hoffmann et al (2017) presented an intercomparison of meteorological analyses and an evaluation of MPTRAC trajectory calculations with superpressure balloon observations for the Antarctic lower stratosphere. Rößler et al (2018) evaluated trajectory errors of different numerical inte-Atmos. Chem.…”
Section: Model Descriptionsmentioning
confidence: 99%
See 2 more Smart Citations